The Role of Spiritual Health in Predicting Stress in Infertile Women Mediated by Resilience - Maryam Safara; Soolmaz Moosavi; Seyed Mahmood Mosavi Nezhad; Seyedeh Mahsa Seyyedi (Mashhad University of Medical Sciences, 2024)
Background & aim: Infertility is a culturally dependent, challenging experience for individuals and families. Understanding characteristics of Iranian infertile couples and effective coping factors can help counselors in selecting appropriate models. This study assesses the role of spiritual health in predicting stress in infertile women through resilience mediating role.Methods: This predictive correlational study was conducted on 105 women at gynecology clinics of Mashhad, Iran in 2021.They were selected through Convenience sampling method. Tools included Spiritual Well Being Scale, Connor & Davidson Resilience Questionnaire and, Newton, Schrard, and Glavas Perceived Infertility Stress.  The instrument used were paper and pen, and they were completed by the participants. Pearson correlation coefficient and structural equation modeling were employed to analyze the data using SPSS (version 22) and Smart PLS software (version 3).Results: Findings revealed significant negative and relationships between spiritual health and perceived stress, positive relationships between spiritual health and resilience, and a negative relationship between resilience and perceived stress. Resilience mediated the negative and significant relationship between spiritual health and stress in infertile women. The value of the VAF index was equal to 0.368 and the total effect of spiritual health on perceived stress was equal to -0.732.Conclusion: Spiritual health and resilience effectively reducestress in infertile women. Recommending psychological counseling based on spiritual health and interventions in suggested.